Economic Assessment of a Small-Scale Plant for Production of Sulforaphane-Rich Broccoli Flour in Chile - Mahn-Osses, A; Salazar-Navarrete, J; Quintero-Suarez, J (John Wiley and Sons Ltd, 2020)
Broccoli offers several health benefits due to its high content of bioactive compounds, especially sulforaphane – a promising anticancer compound. In Chile, the broccoli crop is expanding rapidly, creating opportunities to industrialize this vegetable and exploit its functional properties. Various processes have been studied with the aim of maximizing the sulforaphane content in processed broccoli using different dehydration methods. These have shown large differences in terms of recovery and cost. This work shows an economic feasibility study of a small-scale plant for the production of sulforaphane-rich broccoli flour considering three drying alternatives: tray drying (TD), pulsed fluidized-bed drying, and freeze-drying (FD). Freeze drying resulted in the highest sulforaphane content in the broccoli flour; however, this process entails the highest production cost. Tray drying showed the lowest production cost and a comparatively high sulforaphane content in the final product. Pulsed fluidized bed drying (PFBD) resulted in the highest sulforaphane loss. Although the three drying technologies resulted in positive net present values (NPV), the internal rate of return (IRR) was the lowest for freeze drying as a result of the high investment – over 20% higher than the investment required by the other alternatives. The NPV was practically independent of the drying technology when the sulforaphane content was considered in the estimation of the selling price. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd